4CPS-145 Consensus validation of a screening tool for cardiovascular pharmacotherapy in geriatric patients: the rasp_cardio list. Issue 1 (23rd March 2023) - de Schutter, H; Hias, J; Hellemans, L; Walgraeve, K; Tournoy, J; Van Der Linden, L
Abstract : Background and Importance: Cardiovascular therapies have been identified as major culprits for adverse drug events. Their inappropriate (under)use puts geriatric patients at increased risk for avoidable harm. These therapies are used frequently, accounting for approximately half of all prescribed drugs in geriatric patients. Paradoxically, most studies on medication reviews in geriatric patients have not specifically targeted cardiovascular therapies. This might be owing to a lack of resources, training or explicit support to perform targeted medication reviews. Consequently, there is a clear need for an updated screening tool, specifically targeting cardiovascular therapies in geriatric patients. Aim and Objectives: We aimed to update and validate the cardiovascular segment of a previously developed screening tool, the RASP list. The updated RASP_CARDIO list was intended for use in geriatric patients by trained health care professionals. Material and Methods: A three-step study was conducted by a collaboration of the pharmacy, geriatric medicine and cardiology departments of a large, academic hospital. First, the cardiovascular segment of the RASP list (version 2014) was updated taking into account published research, other available screening tools and the input of end-users. Secondly, this draft was reviewed during three panel discussions with five expert cardiologists and three clinical pharmacists, all of whom had relevant expertise in geriatric pharmacotherapy. Thirdly, the content was validated using a modified Delphi Technique by a panel of European hospital pharmacists, cardiologists, geriatricians and an internal medicine physician. Consensus was achieved in case of ≥80% agreement among experts. The final construct was compared to the cardiovascular segment of the STOPP/START criteria version 2. Results: Seventeen experts from four European countries participated in two validation rounds. Consensus was achieved for all statements of the RASP_CARDIO list. One new statement was added. The final construct comprised a list of 95 statements related to potentially inappropriate prescribing of cardiovascular agents. Approximately 90% (29/32) of the cardiovascular statements of the second version of the STOPP/START criteria were included in the RASP_CARDIO list and the RASP_CARDIO list had 66 additional statements. Conclusion and Relevance: The RASP_CARDIO list is an updated and validated explicit screening tool to optimise cardiovascular pharmacotherapy in geriatric patients. References and/or Acknowledgements: Conflict of Interest: No conflict of interest